PEMANFAATAN TANAMAN HERBAL SEBAGAI IMUNOMODULATOR PADA MASA PANDEMI COVID-19 DI KELURAHAN SUKODONO KABUPATEN GRESIK - ERNAWATI, ERNAWATI ERNAWATI; Sulastri, Sulastri; Zuhroh, Diah Fauzia (Universitas Muhammadiyah Gresik, 2021)
Background, Coronavirus Disease 2019 (COVID-19) has been declared by WHO as a global pandemic and in Indonesia it is declared as a type of disease that causes public health emergencies and non-natural disasters. Judging from the situation of the spread of COVID-19 which has almost reached all provinces in Indonesia with the number of cases and/or the number of deaths increasing and having an impact on the political, economic, social, cultural, defense and security aspects, as well as the welfare of the people in Indonesia, it is necessary to countermeasures, including prevention and control. Gresik Regency is one of the regions in East Java where there has been a significant and rapid increase and spread of Corona Virus Disease 2019 (COVID-19) cases so that it is included in the red zone. As of Tuesday, July 21, 2020, Gresik Regency recorded 1,495 Covid-19 cases, of which 887 patients were still being treated, 479 patients recovered, and 129 patients died. Efforts to prevent the spread of covid-19 by applying discipline to health protocols and increasing body immunity, increasing the immune system through the use of medicinal plants such as;Temulawak, basil and moringa. Aim, provide knowledge to the community of Sukondono Village, Gresik Regency about the use of herbal plants as immunomodulators during the COVID-19 pandemic. Methods; (1) socialization is carried out by the community service team from the Universitas Muhammadiyah Gresik with the ranks of the Government in Gresik Regency. (2) implementation of activities using lecture, practice, and discussion methods. (3) the evaluation of the activities was carried out 2 times, namely pre-test and post-test. The results of the evaluation were analyzed using a paired sample T test with a limit of significance (α 0.05). Service activities in Sukodono sub-district, Gresik district, with a total of 40 participants. Results, based on the pairet analysis of the T test, the average value of the pre-test was 57,025 and the post-test was 72,950. While the value of sig 2 tailed shows 0.000 < 0.05. Conclusion, there was an increase in knowledge of participants after being given counseling about the use of herbal plants as immunomodulators during the covid-19 pandemic.